La formation des réseaux intra ethniques au sein des communautés d’immigrés Latinos : analyse comparative de Miami et Los Angeles - Marie L. Mallet (L'Ordinaire des Amériques)
This paper investigates the formation of social networks in the Latino communities of Los Angeles and Miami. In order to better understand how Latino immigrants adapt to the host society, this article offers a comparative analysis of the interactions within the different Latino communities and puts forward their role on the formation of social networks among Latino immigrants in these cities. The results show that social networks are highly dependent on the dynamics within the Latino communities as well as the urban context; these networks, their strength, and development differ in Los Angeles and Miami based on factors such as socioeconomic status, levels of segregation and ethnic concordance among the Latino communities.